2019
DOI: 10.1038/s41598-019-41999-0
|View full text |Cite
|
Sign up to set email alerts
|

Wave attenuation and trapping in 3D printed cantilever-in-mass metamaterials with spatially correlated variability

Abstract: Additive manufacturing has become a fundamental tool to fabricate and experimentally investigate mechanical metamaterials and phononic crystals. However, this manufacturing process produces spatially correlated variability that breaks the translational periodicity, which might compromise the wave propagation performance of metamaterials. We demonstrate that the vibration attenuation profile is strictly related to the spatial profile of the variability, and that there exists an optimal disorder degree below whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 59 publications
2
31
0
1
Order By: Relevance
“…It should also be noted that for increasingly steeper variations of the masses of the resonators, there is band gap annihilation related to the level of disorder degree. It has been shown that this is caused by internal wave trapping phenomena [52] due to the existing critical sections, i.e. local changes from propagating to nonpropagating waves [53].…”
Section: Metamaterials Beams With Symmetric Rainbow-shaped Cantilever-mentioning
confidence: 99%
“…It should also be noted that for increasingly steeper variations of the masses of the resonators, there is band gap annihilation related to the level of disorder degree. It has been shown that this is caused by internal wave trapping phenomena [52] due to the existing critical sections, i.e. local changes from propagating to nonpropagating waves [53].…”
Section: Metamaterials Beams With Symmetric Rainbow-shaped Cantilever-mentioning
confidence: 99%
“…The differences between the experimental and analytical results are mainly the bandgap frequencies, which might be caused by the uncertainties of experimental conditions and 3D manufacturing process. Especially, the dimension and physical parameter variabilities introduced by the 3D printing process are found to have greatly influenced the FRFs of rainbow metamaterial [51], which will be explored specifically in further work.…”
Section: Analytical Predictions Of the Frfs Of Rainbow Metamaterialsmentioning
confidence: 99%
“…Currently, there is few experimental work available in the literature investigating metamaterial performance for vibration attenuation applications (e.g. [5][6][7][8][9][10]) and most of them do not consider the effects of spatially correlated disorder on the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-resonators design have also been explored in more complex structures with encouraging results for industrial applications [9,10]. It has been shown that the break of periodicity introduced by the spatial variability of material and geometrical properties of metastructures creates a resonator mistuning which can induce wave trapping and thus greatly affecting the vibration attenuation performance by either band gap annihilation or attenuation bandwidth widening, depending on the imposed spatial profile [6]. Overall, there is a need to investigate the effects of the manufacturing variability on the performance of metastructures [1,[26][27][28][29], which can also affect the coupling of the metastructures to the vibration source and receiver [30].…”
Section: Introductionmentioning
confidence: 99%